PEMBUATAN DAN KARAKTERISASI KATALIS HETEROGEN SO 2- - ZnO DAN SO42- / ZnO DENGAN METODE KOPRESIPITASI DAN IMPREGNASI UNTUK PRODUKSI BIODIESEL DARI MINYAK KEDELAI - D. A. Rahmawati; D. Intaningrum; Istadi Istadi (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
In this reasearch focuses on the physical and chemical 2- characterization of 2- sulfated zinc oxide catalyst SO4 - ZnO with coprecipitation method and SO4 / ZnO impregnation method. The purpose of this study is to prepare the ZnO-based acid catalyst, to determine the characteristics of the catalyst, and the catalyst testin on biodiesel production from soybean oil. The characterization was conducted using X-ray diffraction (XRD) to determine the catalyst morphology and Fourier Transform-Infra Red (FT-IR) to determine the structure of chemical bonds are formed. Identification of the content and composition of biodiesel, mainly on the composition of Fatty Acid Methyl Ester (FAME), were analyzed by GC-MS and by FT-IR. Meanwhile the heat content of the products of 2- biodiesel calorific value is measured. Results of the characterization showe that the SO4 2- - ZnO catalyst has a stronger acidity and higher catalyst activity than acidic SO4 / ZnO catalysts. In the catalyst testing for the transesterification process, the SO42–ZnO catalyst showed the biodiesel yield of 80.19%.